2020
DOI: 10.1093/mnras/staa968
|View full text |Cite
|
Sign up to set email alerts
|

GASP XXV: neutral hydrogen gas in the striking jellyfish galaxy JO204

Abstract: We present JVLA-C observations of the H i gas in JO204, one of the most striking jellyfish galaxies from the GASP survey. JO204 is a massive galaxy in the low-mass cluster A957 at z = 0.04243. The H i map reveals an extended 90 kpc long ram-pressure stripped tail of neutral gas, stretching beyond the 30 kpc long ionized gas tail and pointing away from the cluster centre. The H i mass seen in emission is $(1.32\pm 0.13) \times 10^{9} \, \rm M_{\odot }$, mostly located in the tail. The northern part of the galax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 93 publications
3
44
0
Order By: Relevance
“…A lot of observational evidence indicates that this process, which is commonly referred to as ram pressure stripping (Gunn & Gott 1972), dominates the evolution of gas-rich late-type systems in nearby massive clusters (e.g., Boselli & Gavazzi 2006, 2014; this evidence includes the presence of galaxies with long cometary tails in the various gas phases (atomic cold, e.g., Chung et al 2007;ionised, Yagi et al 2010;hot, e.g., Sun et al 2007) without any associated stellar counterpart or the high frequency of spirals with radially truncated gaseous discs (e.g., Cayatte et al 1994;Koopmann & Kenney 2004). While many representative objects undergoing a ram pressure stripping event have been already studied in detail using multi-frequency observations (Kenney et al 2004(Kenney et al , 2014(Kenney et al , 2015Crowl et al 2005;Boselli et al 2016a;Sun et al 2006Sun et al , 2007Sun et al , 2010Merluzzi et al 2013;Abramson & Kenney 2014;Abramson et al 2011Abramson et al , 2016Jáchym et al 2013Jáchym et al , 2014Jáchym et al , 2017Jáchym et al , 2019Fumagalli et al 2014;Fossati et al 2016;Poggianti et al 2019;Bellhouse et al 2019;Deb et al 2020;Moretti et al 2020a) and tuned models and simulations (Vollmer et al 1999(Vollmer et al , 2000(Vollmer et al , 2004a(Vollmer et al ,b, 2006(Vollmer et al , 2008a(Vollmer et al ,b, 2012(Vollmer et al , 2018Roediger & Hensl...…”
Section: Introductionmentioning
confidence: 99%
“…A lot of observational evidence indicates that this process, which is commonly referred to as ram pressure stripping (Gunn & Gott 1972), dominates the evolution of gas-rich late-type systems in nearby massive clusters (e.g., Boselli & Gavazzi 2006, 2014; this evidence includes the presence of galaxies with long cometary tails in the various gas phases (atomic cold, e.g., Chung et al 2007;ionised, Yagi et al 2010;hot, e.g., Sun et al 2007) without any associated stellar counterpart or the high frequency of spirals with radially truncated gaseous discs (e.g., Cayatte et al 1994;Koopmann & Kenney 2004). While many representative objects undergoing a ram pressure stripping event have been already studied in detail using multi-frequency observations (Kenney et al 2004(Kenney et al , 2014(Kenney et al , 2015Crowl et al 2005;Boselli et al 2016a;Sun et al 2006Sun et al , 2007Sun et al , 2010Merluzzi et al 2013;Abramson & Kenney 2014;Abramson et al 2011Abramson et al , 2016Jáchym et al 2013Jáchym et al , 2014Jáchym et al , 2017Jáchym et al , 2019Fumagalli et al 2014;Fossati et al 2016;Poggianti et al 2019;Bellhouse et al 2019;Deb et al 2020;Moretti et al 2020a) and tuned models and simulations (Vollmer et al 1999(Vollmer et al , 2000(Vollmer et al , 2004a(Vollmer et al ,b, 2006(Vollmer et al , 2008a(Vollmer et al ,b, 2012(Vollmer et al , 2018Roediger & Hensl...…”
Section: Introductionmentioning
confidence: 99%
“…The GASP survey 9 (Poggianti et al 2017b) has started exploring the effects of environmental interactions on nearby (z 0.05) cluster/group galaxies thanks to a dedicated VLT MUSE Large Program (GAs Stripping Phenomena in galaxies with MUSE, P. I. B. Poggianti) mainly tracing the ionized gas, but complementary data sets at different wavelengths are being collected and have started offering a clear view on all the connected gas phases (see also George et al 2018;Poggianti et al 2019;Ramatsoku et al 2019Ramatsoku et al , 2020Deb et al 2020). In particular, in Moretti et al (2018) we observed with the APEX telescope 4 GASP galaxies detecting molecular gas both in the galaxy disks and in the ionized gas tails.…”
Section: Introductionmentioning
confidence: 99%
“…Jáchym et al 2013Jáchym et al , 2014Jáchym et al , 2017Scott et al 2013Scott et al , 2015Verdugo et al 2015;Moretti et al 2018), and H I (e.g. Oosterloo & van Gorkom 2005;Chung et al 2007Chung et al , 2009Scott et al 2010Scott et al , 2012Abramson & Kenney 2014;Kenney et al 2014;Ramatsoku et al 2019;Serra et al 2019;Deb et al 2020). Extensive simulations (e.g.…”
mentioning
confidence: 99%